Global lung cancer burden, trends, and projections from 2010 to 2050: A population-level severity framework integrating DALYs-per-case and mortality-to-incidence ratio - Omar Freihat; Maria Aamir; Zsolt Cselik; Arpad Kovacs; David Sipos (PLoS ONE, 2026)
Background Lung cancer remains the leading cause of cancer mortality worldwide. While incidence and mortality describe population burden, they do not fully capture disease severity at the level of the individual patient. This study quantified the contemporary global burden, temporal trends, and future trajectory of tracheal, bronchus, and lung (TBL) cancer, and applied a multidimensional severity framework integrating fatal and non-fatal outcomes. Methods A global ecological analysis was conducted across 185 countries and territories using harmonized data from GLOBOCAN 2022, the Global Burden of Disease (GBD) 2023 study, and the UN World Population Prospects 2024. Contemporary burden was assessed using incident cases, deaths, age-standardized incidence and mortality rates (ASIR/ASMR), disability-adjusted life years (DALYs), mortality-to-incidence ratio (MIR), and DALYs per incident case. Temporal trends in ASIR and ASMR (2010–2023) were estimated using log-linear regression to derive average annual percent change (AAPC). Projections to 2050 were generated under two scenarios: (1) constant 2022 rates reflecting demographic change only, and (2) trend-based projections extrapolating country-specific AAPCs. Disease severity was evaluated using a two-dimensional framework combining MIR and DALYs-per-case, which captures average lifetime health loss per diagnosed individual independent of population size or age structure. Results In 2022, an estimated 2.48 million new TBL cancer cases and 1.82 million deaths occurred globally, corresponding to ASIR and ASMR of 23.6 and 16.8 per 100,000, respectively. Global DALYs reached 46.7 million, yielding 18.8 DALYs per case, with substantially higher burden in males and in higher-SDI regions. From 2010-2023, age-standardized rates increased in most low- and middle-income countries and declined predominantly in high-income settings. By 2050, demographic change alone is projected to drive large increases in burden in many low-resource countries, with further amplification under trend-based scenarios. DALYs-per-case showed a moderate positive correlation with MIR (Spearman’s r_s = 0.46), revealing marked heterogeneity in severity profiles across countries. Conclusions Global lung cancer burden is projected to rise substantially in many regions despite declining rates in high-income settings. Integrating DALYs-per-case with MIR provides a complementary severity lens that highlights inequities not captured by incidence and mortality alone and supports more targeted prevention, treatment, and survivorship strategies.